UNRAVELING THE DYNAMICS OF INTERCULTURAL COMMUNICATION AND ADAPTATION PROCESSES IN MULTICULTURAL SETTINGS - Tri, Nguyen Minh (Universitas Padjadjaran, 2024)
The purpose of this article is to provide an explanation of the concept of intercultural communication and its nature while also identifying the crucial cultural adaptation process. The study used a qualitative literature search method to form and analyse the adaptation process in intercultural communication. Additionally, the article emphasises that culture shock plays a significant role in the dynamics of the adaptation process. Moreover, it points out that every individual faces distinct challenges during each phase of the adaptation process.